Transcendence : on self-determination and cosmopolitanism - Aboulafia, Mitchell (Stanford University Press, 2010)
Transcendence offers an original theory of self and society that reconciles philosophical and political commitments to self-determination, cultural pluralism, and cosmopolitanism.